PENINGKATKAN AKTIVITAS BELAJAR BAHASA INDONESIA MELALUI MODEL DISCOVERY LEARNING PADA SISWA KELAS VII.1 SMPN 3 KOTO BARU - Noviana, Rina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This study aims to improve Indonesian language learning activities through the application of discovery learning models to class VII.1 students of SMPN 3 Koto Baru. Classroom action research was carried out for two cycles, with each cycle holding two meetings. Each meeting is held by applying the discovery learning model. As a data collection tool is the result of observation of student learning activities in cycle 1 and cycle 2. The results of research obtained on student learning activities at the initial observation of 68% categories (less active), increased 80% categories (active) in the first cycle, and increased again 85% (active) category in cycle II. Learning activities of students learning Indonesian experience an improvement from the first cycle to the second cycle, this shows that the discovery learning model can be used as an alternative learning to improve student learning activities.